2021
DOI: 10.1371/journal.pone.0255380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychogenic stress on some peripheral and central inflammatory markers in rats with the different level of excitability of the nervous system

Abstract: Patients with post-stress pathologies display the signs of inflammation in the peripheral blood as well as in the brain. The mechanisms of such post-stress neuroimmune changes, their contribution to the behavior, the relationship of the intensity of inflammation with genetically determined features have not been clarified. The goal of this work was to evaluate the dynamics of post-stress inflammation in the blood and hippocampus of rats which differ in level of excitability of the nervous system. Rats of two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…A higher blood level of il 1β mRNA expression was detected in highly excitable LT rats compared to low excitable HT animals. This is consistent with our previous data that highly excitable rats develop signs of inflammation in the blood in response to chronic stress, as manifested in changes in the leukocyte formula [13].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A higher blood level of il 1β mRNA expression was detected in highly excitable LT rats compared to low excitable HT animals. This is consistent with our previous data that highly excitable rats develop signs of inflammation in the blood in response to chronic stress, as manifested in changes in the leukocyte formula [13].…”
Section: Discussionsupporting
confidence: 93%
“…The obtained results are in good agreement with the data avail able in the literature that in the CNS, unlike at the periphery, high GC doses or long term stress lead to an increased production of inflammatory mediators and microglia activation [7,17]. We have previously shown [13] that the number of microglial cells increases 7 days after stress expo sure in the dentate gyrus (DG), hippocampal CA1 and CA3 fields in LT rats and in the CA1 field in HT animals, which does not contemporize with the increase in the level of il 1β gene expression observed in the present work, as it occurs only on day 24 against a normalization of the number of microglial cell. Activation and proliferation of microglia, as well as blood-brain monocyte traf ficking, being the main sources of IL 1β and TNF, occur after some latent period, and this may account for the delay described above.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The number of Iba+ cells in the dentate gyrus also did not change after stress, but house mice had significantly more microglia than C57BL/6 animals. In our previous study with two rat strains with different levels of excitability of the nervous system [51], we have shown that animals of the highly excitable strain had significantly less Iba+ cells in the hippocampus than the less excitable strain [52]. Highly excitable rats seemed to be more susceptible to immune dysfunctions in response to chronic stress.…”
Section: Discussionmentioning
confidence: 85%